Fascia Is Able to Actively Contract and May Thereby Influence Musculoskeletal Dynamics: A Histochemical and Mechanographic Investigation - Schleip, Robert; Gabbiani, Giulio; Wilke, Jan; Naylor, Ian; Hinz, Boris; Zorn, Adjo; Jäger, Heike; Breul, Rainer; Schreiner, Stephanie; Klingler, Werner (Frontiers in Physiology, 2019)
Fascial tissues form a ubiquitous network throughout the whole body, which is usually regarded as a passive contributor to biomechanical behavior. We aimed to answer the question, whether fascia may possess the capacity for cellular contraction which, in turn, could play an active role in musculoskeletal mechanics. Human and rat fascial specimens from different body sites were investigated for the presence of myofibroblasts using immunohistochemical staining for -smooth muscle actin (n= 31 donors, n=20 animals). In addition, mechanographic force registrations were performed on isolated rat fascial tissues (n=8 to n=18), which had been exposed to pharmacological stimulants. The density of myofibroblasts was increased in the human lumbar fascia in comparison to fasciae from the two other regions examined in this study: fascia lata and plantar fascia (H(2) = 14.0, p < 0.01). Mechanographic force measurements revealed contractions in response to stimulation by fetal bovine serum, the thromboxane A2 analog U46619, TGF-β1, and mepyramine, while challenge by botulinum toxin type C3–used as a Rho kinase inhibitor– provoked relaxation (p<.05). In contrast, fascial tissues were insensitive to angiotensin II and caffeine (p>.05). A positive correlation between myofibroblast density and contractile response was found (r=.83, p<.001). The hypothetical application of the registered forces to human lumbar tissues predicts a potential impact below the threshold for mechanical spinal stability but strong enough to possibly alter motoneuronal coordination in the lumbar region. It is concluded that tension of myofascial tissue is actively regulated by myofibroblasts with the potential to impact active musculoskeletal dynamics.